Chemistry - Chang, Raymond; Goldsby, Kenneth A. (McGraw-Hill, 2013)
Designed for the two-semester general chemistry course, this book continues the tradition of providing a firm foundation in chemical concepts and principles while presenting a broad range of topics in a clear, concise manner